Unveiling the nexus: Understanding socio-ecological determinants of children’s sensitivity and vulnerability to climate change - Joseph, Laurent (Universitas Airlangga, 2025)
Children in every corner of the globe face climate change challenges, including Tanzania. This study explores the socio-ecological factors that predisposed and made children more sensitive to climate change's impact in Longido District, Tanzania. The study was guided by social vulnerability, resilience, and intersectionality theories, among others, and employed the mixed-methods design comprising household survey and focus group discussions in data collection with a sample size of 123 respondents. The study's findings indicate that several social and ecological factors shape the impact of climate change on children, such as water stress, inundation, disease and pest outbreaks, food insufficiency, whirling of air, threats to livelihoods, drought, extreme heat, and many more. Also, this research revealed various strategies in which children's vulnerability to climate change is lessened. These include improving clean drinking water, sanitation, and health services, building schools, introducing climate-smart agriculture, and education. They aim to reduce and lessen climate change's effect on children in areas with the same characteristics. Therefore, the study recommends collaboration among policymakers, local authorities, and other players to implement integrated and location-specific strategies that address children's issues in climate change-affected regions.